Cementovaný dřík TEP Poldi-Čech po 25 letech - Rozkydal, Zbyněk; Janíček, Pavel (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2010)
PURPOSE OF THE STUDY The aim of the study was to evaluate the results of Poldi-Čech femoral stem implantation in primary total hip arthroplasty after 25 years. MATERIAL AND METHODS A group of 65 patients (90 hips) with Poldi-Čech total hip arthroplasty carried out between 1974 and 1984 was evaluated at the end of 2009. The mean follow-up of all patients was 28 years (25 to 35). There were seven men and 58 women. The mean age at the time of implantation was 43 years (26 to 60) and at the latest follow-up it was 72 years. In all patients the cemented UHMW PE acetabular component (RCH 1000) was used together with AKV Ultra 2 Poldi steel femoral stems (1st, 2nd and 3rd generations). The stem was a monoblock with a 32-mm head. The evaluation of the results was based on the Harris hip score and X ray with an A-P view of the pelvis and the affected hip. Statistical analysis was made using the life-table method. RESULTS At the latest follow up the mean Harris score was 69.7 points (40 to 88). There were 69 hips with an original Poldi-Čech femoral component still in situ, 64 of them were stable and five with radiological evidence of aseptic loosening. Five patients had undergone Girdlestone resection arthroplasty for septic loosening. Thirteen patients (16 hips) had femoral stem revision. The cumulative proportion of clinical survivorship of the Poldi-Čech femoral stem, with revision for any reason as the endpoint, .was 0.93 at 6 years, 0.84 at 12 years, and 0.77 at 18, 24 and 30 years after the index surgery. Radiograp-hic findings revealed 64 hips with stable stems, five hips with ;aseptic loosening (probable, 0 possible, 2, definite, 3). Sixteen hips were after revision surgery for aseptic loosening of the stem and five hips were after Girdlestone resection arthroplasty for septic failure. The cumulative proportion of radiological survivorship of the Poldi-Čech femoral stem with any reason as the endpoint was 0.92 at 6 years, 0.78 at 12 years, 0.72 at 18 years, 0.69 at 24 years and 0.69 at 30 years. DISCUSSION The Poldi-Čech stem with its anatomical shape and a highly polished surface meets the principles of successful composite beam stems. Its disadvantage is a valgus neck-shaft angle of 140° giving lower femoral offset and the risk of development of valgus deformity of the ipsilateral knee. In most cases osteolysis, radiolucent lines and bone rarefaction of the femur resulted from polyethylene wear of the acetabular component. CONCLUSIONS This study demonstrates a long-term survivorship of the Poldi-Čech femoral component in patients undergoing total hip arthroplasty 25 to 35 years ago.
Keywords: dospělí; Female; kyčelní kloub; kyčelní protézy; Adult; ženské pohlaví; lidé; Femur; následné studie; cementování; Reoperation; femur; reoperace; Hip Joint; Follow-Up Studies; selhání protézy; Cementation; Male; Aged; náhrada kyčelního kloubu; Arthroplasty, Replacement, Hip; senioři; mužské pohlaví; Hip Prosthesis; Prosthesis Failure; Humans